The (real) revolution in military affairs - Martyanov, Andrei, 1963- (Clarity Press, 2019)
"The (Real) Revolution in Military Affairs provides deep insight into the technological evolution of weapons and its impact on international relations in the 20th and 21st centuries. The United States' efforts to preserve not just its dominance but the perception of its dominance are bound to fail for many important reasons. None are more important than what is often misidentified in the past American military-theoretical hypotheses as the future of warfare, known generically as the Revolution in Military Affairs (RMA). This book explains why those hypotheses are failing and will continue to fail, and addresses the real RMA. In the end, technological development in weaponry as a response to tactical, operational and strategic requirements defines not only a nation's geopolitical status but determines the global order." P. [4] of cover